Bank Emok: Conflict Analysis and Sustainable Solution Efforts from the Perspective of Risk Society Theory - Nugraha, Aji Satria; Suhada, Djilzaran Nurul (The Eastasouth Journal of Social Science and Humanities, 2024)
Bank Emok is a term for the people of Solear District, Tangerang Regency, Banten Province for institutions that are similar to conventional banks in general, but these banks are illegal and owned by individuals who rely on loan sharks to run their operating systems. This research attempts to describe the phenomenon of the increasing number of customers from Bank Emok who are trapped in debt with large interest rates, making it difficult for them to escape. This research uses qualitative methods with a case study approach and analysis of Ulrich Beck's community risk theory to be able to see and investigate more deeply the phenomena that occur in the community of Solear District, Tangerang Regency, Banten. From the analysis of the data obtained, the researcher outlined a strategy to ensure that regional governments, the private sector, and the community escape the trap of the Bank Emok because it has been proven that in several areas of West Java, there are often conflicts between the community and the bank.